The economics of the postal system : alternatives and reform - Sorkin, Alan L. (Lexington, Mass. : Lexington Books, 1980)
Chapter 1 presents an economic history of the postal service. Chapters 2 and 3 describe the present postal service, and analyze trends in postal service financing respectively. Chapter 4 considers the methods used by the postal service to establish rates and allocate costs. Chapter 5 focuses on the postal work force. Chapter 6 analyzes the development of the bulk-mail system. Chapter 7 examines the possible role of the postal service in an electronic mail system. Chapter 8 weighs arguments for and against retention of the postal monopoly on first-class mail and discusses the growth of private postal-service firms. Chapter 9 appraises the work of the postal rate commission. Chapter 10 considers recent legislative proposals relating to postal service activities. The final chapter represents recommendations for change regarding a number of postal service activities.
Includes bibliographical references and index.
ne 23/01/2019
Loans
Keywords: Postal service